Puitisasi Ajaran Islam: Analisis Tekstual Nadoman Akhlak karya Kiai Muhyidin Limbangan (1903-1980) - Gunawan, Aditia (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2019)
This article will discuss the work of a scholar who has never been mentioned in Islamic literature in West Java. He is Kiai Muhyidin (1903-1980) from Limbangan, Garut. His work is calledÂ Nazmul Hujah, or commonly referred to among santri asÂ Nadoman Akhlak. The selection of this work is mainly due to the absence of a special study of the author and his work. In fact, this work is interesting enough to be studied further because it shows the author's attempt to translate the great works of Imam al-GhÄzÄli,Â Iá¸¥yÄ â€˜ulum al-din, even though only a small part of it is in Sundanese, and in poetic form. This research will first discuss in passing the termsÂ nadoman, pupujian, andÂ syi'iran. Then, the author will introduce the biography of Kiai Muhyidin through a review of the text in the Den Maki collection autograph script and interview. Finally, one of his works,Â Nadoman Akhlak, will be explored through textual analysis. In the broader Sundanese-Islamic context, this work is another example of the indigenous efforts of Islam as a Sundanese identity, through efforts to translate Arabic works into languages that were easily understood by Sundanese santriâ€™s.Keywords:Â Nadoman Akhlak,Â Poetization,Â textual analysis,Â Kiai Muhyidin, LimbanganÂ Artikel ini akan membicarakan karya seorang ulama yang selama ini belum pernah disebut-sebut dalam literatur Islam di Jawa Barat. Ulama tersebut adalah Kiai Muhyidin (1903-1980) yang berasal dari Limbangan, Garut. Karyanya berjudulÂ Nazmul Hujah, atau biasa disebut di kalangan santri sebagaiÂ Nadoman Akhlak.Â Pemilihan karya ini terutama disebabkan belum adanya kajian secara khusus terhadap penulis dan karyanya. Padahal, karyanya ini cukup menarik untuk dikaji lebih lanjut karena menunjukkan usaha penulis untuk menerjemahkan karya besar Imam al-GhÄzÄli,Â Iá¸¥yÄ â€˜ulum al-dÄ«n, meski hanya bagian kecilnya saja ke dalam bahasa Sunda, serta ke dalam bentuk puisi. Penelitian ini pertama-tama akan membahas secara sepintas tentang istilahÂ nadoman,Â pupujian, danÂ syiâ€™iran. Kemudian, penulis akan memperkenalkan biografi Kiai Muhyidin melalui telaah teks dalam naskah autograf koleksi Den Maki dan wawancara. Terakhir, salah satu karyanya,Â Nadoman Akhlak, akan dikupas melalui analisis tekstual. Dalam konteks Sunda-Islam yang lebih luas, karya ini merupakan sebuah contoh lain dari usaha membumikan Islam ke dalam identitas Sunda, melalui usaha penerjemahan karya Arab ke dalam bahasa yang mudah dipahami oleh masyarakat.Kata kunci:Â Nadoman Akhlak,Â puitisasi, analisis tekstual, Kiai Muhyidin, Limbangan